SKABIES NORWEGIAN PADA ANAK DENGAN LUPUS NEFRITIS - Amanda Gracia Manuputty (PAMERI, 2021)
Introduction: Norwegian (crusted) scabies is one of the classic infectious variants of scabies. This variant is common in immunocompromised patients including autoimmune diseases who are taking long-term steroids. Method:We report a case of Norwegian scabies in a child with lupus nephritis.Case:A 15-year-old boy, weighing 40 kg with the chief complaint of black-red spots and thick scales on both fingers, pubic, armpit and body accompanied by itching especially at night. Complaints of night itching were also felt by the patient's mother. The patient had a history of lupus nephritis who was treated with long-term steroids. The results of microscopic examination of skin scrapings found adult mites, eggs and Sarcoptes scabiei schibala. The diagnosis of Norwegian scabies is based on anamnesis, physical and microscopic examination. Results: he patient was treated with 5% permethrin cream, 2-4 ointment 2x a day, cetirizine 1 x 10 mg per day for 2 weeks and education on maintaining personal and environmental hygiene gave healing to the patient. Conclusion: Norwegian scabies therapy is a combination of topical scabidal agents, keratolytic agents to facilitate drug penetration and antihistamines to reduce nocturnal pruritus and education provides clinical improvement and prevents recurrence.